Formation method of sodium ion battery and sodium ion battery
By adopting the step-by-step current charging and discharging method at constant pressure and temperature, SEI and CEI films with distinct structural hierarchies are formed, which solves the film formation instability problem during the sodium ion battery formation process, and achieves efficient transformation and stability improvement of the battery.
Patent Information
- Application Number
- CN202510311502.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-14
- Publication Date
- 2025-07-11
AI Technical Summary
The existing sodium ion battery synthesis method is difficult to ensure film formation stability in large-scale production, and the simplification of the solution becomes unstable and complex of the solution becomes difficult to implement.
The process of forming a step-type current charging and discharging under constant pressure and temperature is adopted to form a negative electrode SEI film with distinct structures and a stable positive electrode CEI film, including a multi-step charging and discharging process at a constant pressure P and a constant temperature T.
It improves the first-effect and cycle stability of sodium ion batteries, improves discharge capacity and cycle stability, and is suitable for large-scale production.
Smart Images

Figure CN120300334A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of batteries, and particularly to a formation method for sodium-ion batteries and sodium-ion batteries. Background Art
[0002] The working principle of sodium-ion batteries is similar to that of lithium-ion batteries. Energy release and storage are achieved through the reversible insertion and extraction of sodium ions between the positive and negative electrodes. Due to advantages such as the wide availability of sodium resources, excellent rate performance, a relatively broad operating temperature range, and safety and stability, sodium-ion batteries can partially replace lithium-ion batteries and lead-acid batteries in the fields of new energy storage and small power batteries, and have broad application prospects.
[0003] As an essential step in the production of sodium-ion batteries, due to differences in the environment and set process conditions, the performance of the negative electrode SEI film formed will vary, which is manifested as having a positive or negative impact on the initial efficiency and cycle life of sodium-ion batteries.
[0004] In existing formation systems, basically, the assembled sodium-ion batteries are formed based on small current charging and its optimized derivative methods, including different currents matching different ambient temperatures and clamping pre-tightening forces, etc. However, these formation methods are relatively cumbersome and are only applicable to experimental properties with low production requirements. In actual industrial production, it is difficult to frequently change the environment or stress to which the battery is subjected. Therefore, an efficient formation method that ensures the stability of battery formation and is applicable to large-scale production with a certain production efficiency is needed. Summary of the Invention
[0005] The present invention provides a formation method for sodium-ion batteries. This formation method does not require frequent changes to the environment or stress to which the battery is subjected, solving the dilemma in the prior art that the film formation of simple formation schemes is unstable and the implementation of complex formation schemes is difficult.
[0006] The present invention also provides a preparation method for sodium-ion batteries. Since this preparation uses the above specific formation method, the obtained sodium-ion batteries have a negative electrode SEI film with distinct structural levels and a stable positive electrode CEI, which helps to improve their initial efficiency and cycle stability.
[0007] The present invention also provides a sodium-ion battery. Since this sodium-ion battery is formed using a specific formation method, it has excellent discharge capacity and cycle stability.
[0008] Specifically, in the first aspect, the present invention provides a formation method for sodium-ion batteries, including: performing the following steps under the conditions of constant pressure P and constant temperature T:
[0009] 1) Charging the sodium-ion battery at a constant current of rate C1 to a cut-off voltage V C1, leave it static for the first preset time;
[0010] 2) Charge the sodium-ion battery at a constant current of rate C2 until the cut-off voltage V C2 , leave it static for the second preset time;
[0011] 3) Charge the sodium-ion battery at a constant current of rate C3 until the cut-off voltage V C3 , leave it static for the third preset time;
[0012] 4) Discharge the sodium-ion battery at a constant current of rate C4 until the cut-off voltage V D , and complete the formation;
[0013] Wherein, P satisfies: 1000Kgf ≤ P < 3000Kgf; C1, C2, C3, and C4 are each independently 0.05C - 0.5C.
[0014] Further, the sodium-ion battery includes a positive electrode sheet, a negative electrode sheet, a separator, and an electrolyte; the positive electrode sheet includes a positive electrode material, the positive electrode material includes an O3-phase layered oxide material, the negative electrode sheet includes a negative electrode material, and the negative electrode material includes a hard carbon material; the electrolyte includes a solvent, an electrolyte sodium salt, and an additive.
[0015] Further, the additive includes at least one of fluoroethylene carbonate, vinylene carbonate, 1,3-propane sultone, and 1,3-dioxolane-2-thione.
[0016] Further, the rate C1 is 0.05C - 0.1C;
[0017] and / or, the rate C2 is 0.1C - 0.15C;
[0018] and / or, the rate C3 is 0.1C - 0.5C.
[0019] Further, C1, C2, and C3 increase.
[0020] Further, the cut-off voltage V C1 is 2.2 - 2.6V;
[0021] and / or, the cut-off voltage V C2 is 2.9 - 3.2V;
[0022] and / or, the cut-off voltage V C3 is 3.9 - 4.1V.
[0023] Further, the first preset time, the second preset time, and the third preset time are each independently selected from any value within the range of 5 - 30 min.
[0024] Further, the magnification C4 is 0.05C - 0.3C; the cut-off voltage V D is 1.5 - 2.0V.
[0025] Further, P satisfies: 1000 kgf ≤ P ≤ 1500 kgf;
[0026] and / or, T satisfies: 30°C ≤ T ≤ 40°C.
[0027] In a second aspect, the present invention provides a method for preparing a sodium-ion battery, including forming the sodium-ion battery according to the forming method of the sodium-ion battery described in the first aspect.
[0028] In a third aspect, the present invention provides a sodium-ion battery, which is formed by applying the forming method of the sodium-ion battery described in the first aspect.
[0029] The forming method provided by the present invention does not require frequent changes in the environment or stress to which the battery is subjected, solving the dilemma in the prior art that the film formation of simple forming schemes is unstable and the implementation of complex forming schemes is difficult.
[0030] Further, for the sodium-ion battery provided by the present invention, since the sodium-ion battery adopts a specific forming method for the forming process, therefore, the sodium-ion battery has a layered negative electrode SEI film with distinct density and a stable positive electrode CEI, which helps to improve the initial efficiency and cycle stability of the battery. Description of the Drawings
[0031] The drawings here are incorporated into the specification and constitute a part of this specification, showing embodiments in line with the present invention, and are used together with the specification to explain the principles of the present invention.
[0032] Figure 1 It is a flowchart of the forming process for a specific embodiment of the present invention;
[0033] Figure 2 It is a comparison chart of the AC resistance ACR of sodium-ion batteries obtained by the forming methods of Examples 1 - 4 and Comparative Examples 1 - 3 of the present invention;
[0034] Figure 3 It is a comparison chart of the DC discharge resistance DCR of sodium-ion batteries obtained by the forming methods of Examples 1 - 4 and Comparative Examples 1 - 3 of the present invention;
[0035] Figure 4 It is a comparison chart of the appearance (gas production state) of sodium-ion batteries obtained by the forming methods of Example 1 and Comparative Example 3 of the present invention.
[0036] Through the above-mentioned drawings, specific embodiments of the present invention have been shown, and will be described in more detail hereinafter. These drawings and the written description are not intended to limit the scope of the inventive concept in any way, but to illustrate the concept of the present invention to those skilled in the art by reference to specific embodiments. Detailed Embodiments
[0037] To make the objectives, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the application will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are some, but not all, of the embodiments of the present invention. All other embodiments obtained by those of ordinary skill in the art based on the embodiments in the application without creative efforts shall fall within the protection scope of the present invention.
[0038] In order to ensure the stability of battery formation and apply to large-scale production with a certain production efficiency, the present invention adopts the following technical solutions:
[0039] In a first aspect, the present invention provides a method for forming a sodium-ion battery. The process is shown in Figure 1 , and includes: performing the following steps under the conditions of a constant pressure P and a constant temperature T:
[0040] 1) Charging the sodium-ion battery at a constant current with a rate C1 to a cut-off voltage V C1 , and standing for a first preset time;
[0041] 2) Charging the sodium-ion battery at a constant current with a rate C2 to a cut-off voltage V C2 , and standing for a second preset time;
[0042] 3) Charging the sodium-ion battery at a constant current with a rate C3 to a cut-off voltage V C3 , and standing for a third preset time;
[0043] 4) Discharging the sodium-ion battery at a constant current with a rate C4 to a cut-off voltage V D , and completing the formation;
[0044] Wherein, P satisfies: 1000Kgf ≤ P < 3000Kgf; C1, C2, C3, and C4 are each independently 0.05C - 0.5C.
[0045] In the present invention, first, the battery is charged with a stepped current under a constant pressure P and a constant temperature T, which is beneficial to form a layered SEI film on the negative electrode side of the battery; at the same time, requirements for discharging are put forward, which is beneficial to form a stable CEI film on the positive electrode side of the battery, and the two can synergistically improve the battery stability. Specifically: constant current charging at a rate of C1 can form a dense and stable SEI bottom film mainly composed of inorganic components on the negative electrode side, strengthening the electronic insulation ability of the SEI film; constant current charging at a rate of C2 increases the voltage of the battery, and additives and solvents are reduced to generate an SEI middle film mainly composed of organic components, whose film structure is looser than the SEI bottom film mainly composed of inorganic components, which can strengthen the ion conduction ability of the SEI. Subsequently, constant current charging at a rate of C3 is carried out to form a more porous SEI surface film with stronger ion conduction ability, that is, a layered SEI film is initially formed at this time; finally, the process of constant current discharging at a rate of C4 can, on the one hand, improve the structure of the above-mentioned negative electrode SEI film, and on the other hand, also strengthen the formation of the positive electrode CEI film. The two work together to make the battery more stable and inhibit the subsequent gas generation of the battery. In addition, the battery is at a lower potential after formation, which can also reduce the structural phase change on the positive electrode side during aging at a high potential and reduce the loss of active sodium; in addition, the pressure P within the above range can enable the gas generated by the battery to be discharged in time, while avoiding the increase in the activation energy of sodium ion insertion and reducing sodium deposition, ensuring the integrity of the subsequent film formation.
[0046] In some embodiments, the sodium ion battery includes a positive electrode sheet, a negative electrode sheet, a separator, and an electrolyte; the positive electrode sheet includes a positive electrode material, the positive electrode material includes an O3-phase layered oxide material, the negative electrode sheet includes a negative electrode material, and the negative electrode material includes a hard carbon material; the electrolyte includes a solvent, a sodium salt electrolyte, and an additive.
[0047] Among them, the formation method of the present invention is applicable to various sodium ion batteries, especially applicable to batteries composed of an O3-phase layered oxide positive electrode material and a hard carbon negative electrode material. Such batteries have corresponding reaction peaks during the formation process, and the cut-off voltages of steps 1)-3) can be adjusted according to the reaction peaks.
[0048] "O3" in the above O3-phase layered oxide refers to the arrangement mode of oxygen ions in the crystal structure. More specifically, the O3 structure means that there are three oxygen ion layers in each repeating unit. Exemplarily and not restrictively, the O3-phase layered oxide includes NaNi 0.5 Mn 0.5 O2, NaCoO2, NaFeO2, etc.
[0049] Exemplarily, the above-mentioned positive electrode material further includes a conductive agent and a binder. The conductive agent can be, for example, one or more of conductive carbon black, conductive graphite, carbon nanotubes, and graphene; the binder can be, for example, at least one of carboxymethyl cellulose, styrene-butadiene rubber, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, a polymer containing ethylene oxide, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamideimide, polyvinyl alcohol, and sodium polyacrylate; preferably one or more of carboxymethyl cellulose, styrene-butadiene rubber, polyurethane, polyvinylidene fluoride, polyacrylonitrile, polytetrafluoroethylene, polyvinyl alcohol, polyacrylic acid, polystyrene sulfonate, sodium carboxymethylate, epoxy resin, and vinyl acetate.
[0050] Exemplarily, the above-mentioned negative electrode material further includes a conductive agent, a binder, or a dispersant. The conductive agent can be, for example, one or more of conductive carbon black, conductive graphite, carbon nanotubes, and graphene; the binder can be, for example, at least one of carboxymethyl cellulose, styrene-butadiene rubber, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, a polymer containing ethylene oxide, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamideimide, polyvinyl alcohol, and sodium polyacrylate; preferably one or more of carboxymethyl cellulose, styrene-butadiene rubber, polyurethane, polyvinylidene fluoride, polyacrylonitrile, polytetrafluoroethylene, polyvinyl alcohol, polyacrylic acid, polystyrene sulfonate, sodium carboxymethylate, epoxy resin, and vinyl acetate; the dispersant can be, for example, one or more of carboxymethyl cellulose, triethylhexyl phosphate, sodium dodecyl sulfate, and polyacrylic acid.
[0051] The present invention does not particularly limit the above-mentioned separator, and any publicly known porous structure separator with electrochemical stability and chemical stability can be selected. For example, it can be at least one of glass fiber, non-woven fabric, polyethylene, ceramic coating, polypropylene, or polyvinylidene fluoride; the separator can be single-layer or multi-layer.
[0052] The above-mentioned electrolyte can use Farasis FT-0407-3 or SVOLT NAR01.
[0053] In some embodiments, the additive includes at least one of fluoroethylene carbonate, vinylene carbonate, 1,3-propane sultone, and 1,3-dioxane-2-thione.
[0054] Among them, the above-mentioned additive is more helpful to form a stable SEI film during the formation process. As for the addition amount of the additive, the present invention does not make a special limitation. For example, in the electrolyte, the addition amount of the above-mentioned additive is not higher than 3 wt%.
[0055] It can be understood that the above electrolyte also includes a solvent and a sodium salt electrolyte. The types of the solvent and the sodium salt electrolyte are not particularly limited in the present invention. Those skilled in the art can select conventional sodium salt electrolytes with ion transport and organic solvents with good dispersion effects. In some embodiments, the sodium salt electrolyte includes NaPF6, NaFSI, NaTFSI, NaClO4, NaDFOB, etc.; the solvent includes at least one of ethyl methyl carbonate, diethyl carbonate, and propylene carbonate.
[0056] In some embodiments, the rate C1 is 0.05C - 0.1C;
[0057] and / or, the rate C2 is 0.1C - 0.15C;
[0058] and / or, the rate C3 is 0.1C - 0.5C.
[0059] Among them, the rate range of this embodiment can further ensure that the sodium salt electrolyte forms a more distinct SEI film. Specifically, the SEI surface film near the electrolyte side is porous and loose, having a high ionic conductivity, which allows sodium ions to pass through freely and be smoothly embedded in the negative electrode. The SEI bottom film on the side far from the electrolyte and near the negative electrode coating layer has fewer pores and a compact structure, and its electron isolation characteristics can prevent further reduction reactions of the electrolyte on the negative electrode surface; the SEI film in the middle of the SEI surface film and the SEI bottom film is a transition region between the organic and inorganic components of the SEI film, having appropriate mechanical strength. On the one hand, it combines the two components to form an organic whole, and on the other hand, it improves the flexibility of the overall SEI and reduces the damage to the SEI structure caused by volume changes during charge and discharge.
[0060] In some embodiments, C1, C2, and C3 increase.
[0061] Among them, when the sodium-ion battery is formed at increasing rates of C1, C2, and C3, it can further promote the formation of the SEI film layer structure, thereby further improving the high-temperature cycle performance of the sodium-ion battery. Specifically, during constant-current charging at the low rate C1, a denser and more stable SEI bottom film mainly composed of inorganic components can be formed on the negative electrode side, strengthening the electron insulation ability of the SEI film; then, the current is increased, and constant-current charging is carried out at the rate C2 to rapidly increase the battery voltage, and additives and solvents are reduced to generate an SEI middle film mainly composed of organic components, whose film structure is more porous and can strengthen the ion conduction ability of the SEI. Subsequently, constant-current charging is carried out at the large rate C3 to form a more porous SEI surface film with stronger ion conduction ability.
[0062] In some embodiments, the cut-off voltage V C1 is 2.2 - 2.6V;
[0063] And / or, the cut-off voltage V C2 is 2.9 - 3.2 V;
[0064] And / or, the cut-off voltage V C3 is 3.9 - 4.1 V.
[0065] Among them, the above cut-off voltage V C1 and V C2 respectively correspond to the film-forming reaction peaks of the additive and the solvent. As the charging progresses, the voltage inside the battery will increase. While the SEI film is formed, gas is generated at the same time. Once the gas generation rate is higher than the exhaust rate of the liquid injection hole, the gas will accumulate between the diaphragms inside the battery, resulting in uneven contact between the diaphragm and the negative electrode surface, thus affecting the insertion process of sodium ions on the negative electrode surface. Therefore, within the above range, the cut-off voltage can improve the quality of SEI film formation, improve the first charge-discharge efficiency of the battery, reduce the internal resistance of the battery, and improve the battery cycle performance.
[0066] It should be noted that after each step of the battery, standing for a period of time can eliminate the polarization inside the battery, so that the chemical environment inside the battery tends to be stable, facilitating the battery to perform subsequent steps.
[0067] As for the range of the above standing preset time, the present invention does not make a special limitation. The main purpose of standing is to depolarize when charging to the cut-off voltage. Therefore, the standing preset time can be adjusted according to the actual situation.
[0068] In some embodiments, the first preset time, the second preset time, and the third preset time are each independently any value not less than 5 minutes and not greater than 30 minutes.
[0069] Exemplarily, the first preset time, the second preset time, and the third preset time are 20 minutes. In addition, the first preset value time can also be 7 minutes, 9 minutes, 15 minutes, 18 minutes, 25 minutes, etc.
[0070] In some embodiments, the magnification C4 is 0.05C - 0.3C; the cut-off voltage V D is 1.5 - 2.0 V. Among them, the cut-off voltage V D corresponds to the SOC of the battery ≤ 10%. On the one hand, the lower potential after formation can reduce the structural phase change on the positive electrode side and reduce the loss of active sodium. On the other hand, it can reduce the gas adsorption sites on the negative electrode side and facilitate gas discharge.
[0071] In some embodiments, the P satisfies: 1000 kgf ≤ P ≤ 1500 kgf;
[0072] And / or, the T satisfies: 25°C ≤ T ≤ 40°C.
[0073] Among them, a formation temperature of 25 - 40°C is conducive to the migration of sodium ions and the elimination of battery polarization, avoiding the precipitation of sodium ions on the surface of the negative electrode, thereby affecting battery safety and performance; while a formation pressure of 1000 - 1500Kgf enables the gases generated during the formation of the battery to be discharged in a timely manner, avoiding the gases generated from affecting the contact between interfaces, thereby further improving the stability of battery formation.
[0074] In some embodiments, P is any value among 1000kgf, 1100kgf, 1200kgf, 1300kgf, 1400kgf, 1500kgf, etc. or a range composed of any two of them, and T is any value among 25°C, 27°C, 29°C, 30°C, 32°C, 35°C, 37°C, 39°C, 40°C, etc. or a range composed of any two of them, preferably 30 - 40°C.
[0075] In a second aspect, the present invention provides a method for preparing a sodium - ion battery, including performing formation using the formation method of the sodium - ion battery described in the first aspect.
[0076] In some embodiments, the method for preparing the above - mentioned sodium - ion battery further includes the following steps:
[0077] First step, preparing the positive electrode sheet: The mass ratio of the positive electrode active material, conductive agent, and binder is between 94 - 97:2 - 3:1 - 3, dispersed in an N - methylpyrrolidone (NMP) solvent to obtain a positive electrode slurry. The prepared positive electrode slurry is uniformly coated on the front and back of an aluminum foil with a certain coating surface density, dried, and then roll - pressed according to a certain compaction degree, and the positive electrode sheet is obtained through slitting and die - cutting. Among them, the coating surface density is between 300 - 360g / cm 2 and the aluminum foil is a carbon - coated aluminum foil, and the compaction is between 2.7 - 3.3g / cm 3 .
[0078] Second step, preparing the negative electrode sheet: The proportion of the negative electrode active material, conductive agent, dispersant, and binder is between 91 - 94:2 - 4:1 - 2:2 - 4, dispersed in pure water solvent to obtain a negative electrode slurry. The prepared negative electrode slurry is uniformly coated on the front and back of an aluminum foil with a certain coating surface density, dried, and then roll - pressed according to a certain compaction degree, and the negative electrode sheet is obtained through slitting and die - cutting. Among them, the coating surface density is between 145 - 175g / cm 2 and the aluminum foil is a high - purity aluminum foil, and the compaction is between 0.90 - 0.99g / cm 3 .
[0079] Third step, battery assembly: The positive and negative electrode sheets and the separator are assembled by the Z - shaped laminating method, baked, the electrode tabs are welded, and then encapsulated with an aluminum - plastic film. Finally, liquid injection and aging are carried out.
[0080] Fourth step, battery formation.
[0081] Step 5: Battery aging, exhaust, secondary sealing, and formation.
[0082] Thirdly, the present invention provides a sodium-ion battery, which is formed by using the formation method of the sodium-ion battery described in the first aspect.
[0083] Generally, a sodium-ion battery includes a positive electrode sheet, a negative electrode sheet, a separator, and an electrolyte.
[0084] Among them, the positive electrode sheet includes a current collector and a positive electrode material layer, and the positive electrode material layer includes a positive electrode material, a conductive agent, and a binder.
[0085] Examples of the positive electrode material may include layered oxide materials. Examples of the binder may include at least one of carboxymethyl cellulose, styrene-butadiene rubber, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamideimide, polyvinyl alcohol, and sodium polyacrylate; preferably one or several of polyurethane, polyvinylidene fluoride, polyacrylonitrile, polytetrafluoroethylene, polyvinyl alcohol, polyacrylic acid, polystyrene sulfonate, sodium carboxymethylate, epoxy resin, and vinyl acetate; Examples of the conductive agent may include one or several of conductive carbon black, conductive graphite, carbon nanotubes, and graphene.
[0086] The negative electrode sheet includes a current collector and a negative electrode material layer. The negative electrode material layer includes a negative electrode active material, a conductive agent, a dispersant, and a binder. The negative electrode material is hard carbon. Examples of the conductive agent may include one or several of conductive carbon black, conductive graphite, carbon nanotubes, and graphene; Examples of the binder may include at least one of carboxymethyl cellulose, styrene-butadiene rubber, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamideimide, polyvinyl alcohol, and sodium polyacrylate; preferably one or several of carboxymethyl cellulose, styrene-butadiene rubber, polyurethane, polyvinylidene fluoride, polyacrylonitrile, polytetrafluoroethylene, polyvinyl alcohol, polyacrylic acid, polystyrene sulfonate, sodium carboxymethylate, epoxy resin, and vinyl acetate; Examples of the dispersant may include one or several of carboxymethyl cellulose, triethylhexyl phosphate, sodium dodecyl sulfate, and polyacrylic acid.
[0087] The separator can be any well-known porous structure separator with electrochemical stability and chemical stability. For example, it can be at least one of glass fiber, non-woven fabric, polyethylene, ceramic coating, polypropylene, or polyvinylidene fluoride; the separator can be single-layer or multi-layer.
[0088] The material of the current collector is not specifically limited in the present invention. For example, it can be selected from any one or several of aluminum foil, copper foil, titanium foil, tin foil, chromium foil, and composite foils of the above metals, etc.
[0089] The present invention will be described in detail below in conjunction with specific embodiments:
[0090] The preliminary preparation of the sodium-ion battery involved in the following experiments includes the following steps:
[0091] First step, preparing the positive electrode sheet: Dispersing layered oxide material, conductive carbon black, conductive paste (a mixed paste of carbon nanotubes (CNT) and graphene, with a solid content of 5%, and a mass ratio of CNT to graphene of 8:2), and polyvinylidene fluoride (PVDF) in a mass ratio of 95:2:1:2 in an N-methylpyrrolidone (NMP) solvent to obtain a positive electrode paste with a solid content of 60%. Coating the prepared positive electrode paste evenly on the front and back sides of the aluminum foil with a certain coating surface density, drying it, and then rolling it under a certain compaction. The positive electrode sheet is obtained through slitting and die-cutting. Among them, the coating surface density is 340 g / cm 2 , the aluminum foil is carbon-coated aluminum foil, and the compaction is 2.9 g / cm 3 .
[0092] Second step, preparing the negative electrode sheet: Dispersing hard carbon material, conductive carbon black, carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR) in a mass ratio of 92.5:3:1.5:3 in pure water solvent to obtain a negative electrode paste with a solid content of 50%. Coating the prepared negative electrode paste evenly on the front and back sides of the aluminum foil with a certain coating surface density, drying it, and then rolling it under a certain compaction. The negative electrode sheet is obtained through slitting and die-cutting. Among them, the coating surface density is 164 g / cm 2 , the aluminum foil is high-Guinier optical foil, and the compaction is 0.95 g / cm 3 .
[0093] Third step, battery assembly: Assembling the positive and negative electrode sheets and the separator in a Z-shaped stacking manner, welding the electrode tabs after baking, encapsulating with an aluminum-plastic film, and finally filling with electrolyte and aging. Among them, the separator is a polyethylene (PE) film, and the electrolyte used is Farasis FT-0407-3;
[0094] Fourth step, subjecting the battery after aging to formation according to the schemes of the following examples or comparative examples;
[0095] Fifth step, subjecting the battery after formation to aging, degassing, secondary encapsulation, and grading treatment. The grading treatment is to grade the sodium-ion battery under the condition of 25 ± 2 °C with the following working steps:
[0096] (1) Constant current discharge at 0.1C to the cut-off voltage of 1.5V, and stand for 30 min;
[0097] (2) Charge at a constant current of 0.5C and a constant voltage until the cut-off voltage of 4.0V, with a cut-off current of 0.05C, and then stand for 30 minutes;
[0098] (3) Discharge at a constant current of 0.5C until the cut-off voltage of 1.5V, and then stand for 30 minutes;
[0099] (4) Repeat steps (2) and (3) three times to complete grading.
[0100] Example 1
[0101] This example provides a formation method for a sodium-ion battery. Set the formation fixture pressure to 1200 kgf and the temperature to 35 °C, and perform the following steps:
[0102] 1) Charge the sodium-ion battery at a constant current of 0.05C until the cut-off voltage of 2.4V, and then stand for 20 minutes;
[0103] 2) Charge the sodium-ion battery at a constant current of 0.1C until the cut-off voltage of 3.05V, and then stand for 20 minutes;
[0104] 3) Charge the sodium-ion battery at a constant current of 0.2C until the cut-off voltage of 4.0V, and then stand for 20 minutes;
[0105] 4) Discharge the sodium-ion battery at a constant current of 0.1C until the cut-off voltage of 1.8V to complete the formation.
[0106] Example 2
[0107] This example provides a formation method for a sodium-ion battery. Set the formation fixture pressure to 1000 kgf and the temperature to 30 °C, and perform the following steps:
[0108] 1) Charge the sodium-ion battery at a constant current of 0.05C until the cut-off voltage of 2.4V, and then stand for 20 minutes;
[0109] 2) Charge the sodium-ion battery at a constant current of 0.1C until the cut-off voltage of 3.05V, and then stand for 20 minutes;
[0110] 3) Charge the sodium-ion battery at a constant current of 0.1C until the cut-off voltage of 4.0V, and then stand for 20 minutes;
[0111] 4) Discharge the sodium-ion battery at a constant current of 0.05C until the cut-off voltage of 1.8V to complete the formation.
[0112] Example 3
[0113] This example provides a formation method for a sodium-ion battery. Set the formation fixture pressure to 1500 kgf and the temperature to 40 °C, and perform the following steps:
[0114] 1) Charge the sodium-ion battery at a constant current of 0.1C to the cut-off voltage of 2.4V and let it stand for 20 min;
[0115] 2) Charge the sodium-ion battery at a constant current of 0.15C to the cut-off voltage of 3.05V and let it stand for 20 min;
[0116] 3) Charge the sodium-ion battery at a constant current of 0.5C to the cut-off voltage of 4.0V and let it stand for 20 min;
[0117] 4) Discharge the sodium-ion battery at a constant current of 0.3C to the cut-off voltage of 1.8V to complete the formation.
[0118] Example 4
[0119] Same as Example 1, except that the temperature is 25°C.
[0120] Comparative Example 1
[0121] Same as Example 1, except that the fixture pressure is 0Kgf.
[0122] Comparative Example 2
[0123] Same as Example 1, except that the fixture pressure is 3000Kgf.
[0124] Comparative Example 4
[0125] This example provides a formation method for a sodium-ion battery. Set the formation fixture pressure to 1200 kgf and the temperature to 35°C, and perform the following steps:
[0126] 1) Charge the sodium-ion battery at a constant current of 0.05C to the cut-off voltage of 2.4V and let it stand for 20 min;
[0127] 2) Charge the sodium-ion battery at a constant current of 0.1C to the cut-off voltage of 3.05V and let it stand for 20 min;
[0128] 3) Charge the sodium-ion battery at a constant current of 0.2C to the cut-off voltage of 4.0V and let it stand for 20 min.
[0129] Performance test:
[0130] Test the following performances of the sodium-ion batteries formed according to the above example and comparative example schemes. Some test results are shown in Table 1: Figures 2 - 4 as follows:
[0131] 1) Initial discharge capacity: This value is the sum of the capacity discharged by the sodium-ion battery obtained by formation and the capacity discharged in step 1) of grading.
[0132] 2) Initial efficiency: This value is the ratio of the initial discharge capacity to the sum of the charging capacities in steps 1), 2), and 3) of formation.
[0133] 3) Normal temperature cycle capacity retention rate: At 25 ± 2 °C, charge at a constant current of 0.5C to the cut-off voltage of 3.95V, and let it stand for 30 min; discharge at a constant current of 0.5C to the cut-off voltage of 1.5V, and let it stand for 30 min; cycle 1000 times, and the capacity retention rate is the ratio of the discharge capacity at the 1000th cycle to the discharge capacity at the 1st cycle.
[0134] 4) High temperature cycle capacity retention rate: At 45 ± 2 °C, charge at a constant current of 0.5C to the cut-off voltage of 3.95V, and let it stand for 30 min; discharge at a constant current of 0.5C to the cut-off voltage of 1.5V, and let it stand for 30 min; cycle 500 times, and the capacity retention rate is the ratio of the discharge capacity at the 500th cycle to the discharge capacity at the 1st cycle.
[0135] 5) AC internal resistance ACR: Use the HIOKI BT3562 voltage and internal resistance tester to test the ACR of the battery, and the internal resistance reading is the AC internal resistance.
[0136] 6) DC discharge internal resistance DCR: At 25 ± 2 °C, discharge at a constant current of 0.5C to the cut-off voltage of 1.5V, and let it stand for 30 min; charge at a constant current and constant voltage of 0.5C to the cut-off voltage of 3.95V, with a cut-off current of 0.05C, and let it stand for 30 min; discharge at a constant current of 0.5C for 12 min, with a cut-off voltage of 1.5V, and let it stand for 60 min; discharge at a constant current of 5C for 10 s, with a cut-off voltage of 1.3V, and let it stand for 40 s; charge at a constant current of 5C for 10 s, with a cut-off voltage of 3.95V, and let it stand for 40 s; repeat the above discharge-discharge-charge process 9 times, and the ratio of the voltage difference to the current before and after the 5C discharge step is the DC discharge internal resistance DCR at different SOCs.
[0137] Table 1:
[0138]
[0139] As can be seen from Table 1, compared with the examples, the first discharge capacity of the comparative examples is relatively low, indicating that more active sodium is consumed during the formation process of the battery. Specifically: there is no pressure in Comparative Example 1, and the gas generated by the battery cannot be discharged in time; there is overpressure in Comparative Example 2, resulting in an increase in the activation energy for sodium ion insertion, and a small amount of sodium deposition may occur, etc.; subsequent cycle tests also show that the film formation integrity in the comparative examples is not good. In Comparative Examples 1 and 3, there is a plunge during the cycle, and the battery also generates gas to a certain extent.
[0140] From Figure 2 it can be seen that the ACR of the batteries in Examples 1-3 is relatively low, and the consistency of the batteries is relatively good; the ACR of Comparative Examples 1 and 3 is relatively high, and the consistency of the batteries is not good; the ACR of Comparative Example 2 and Example 4 is in the middle, and the distribution is also relatively concentrated, indicating that the overpressure or the film formation process at normal temperature is still relatively controllable.
[0141] FromFigure 3 It can be seen that under the condition that only the formation process is different, the DCR of the battery can better characterize the film impedance of the battery SEI and CEI. In the figure, the impedance of Examples 1-3 is the lowest, and the impedance of Comparative Examples 1 and 3 is relatively high, indicating that the film formation is relatively imperfect, or abnormal phenomena such as sodium deposition and gas generation occur.
[0142] From Figure 4 It can be seen that due to the absence of the discharge step in Comparative Example 3, the film formation state of the battery is poor. Gas is generated in the battery after formation, and the battery shows slight swelling.
[0143] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, and are not intended to limit them; although the present application has been described in detail with reference to the foregoing embodiments, those of ordinary skill in the art should understand that they can still modify the technical solutions described in the foregoing embodiments, or perform equivalent replacements for some of the technical features; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the spirit and scope of the technical solutions of the embodiments of the present application.
Claims
1. A formation method for a sodium-ion battery, characterized in that, Comprising: The following steps are carried out under the conditions of constant pressure P and constant temperature T: 1) Charge the sodium-ion battery at a constant current of rate C1 to the cut-off voltage V C1 , and let it stand for the first preset time; 2) Charge the sodium-ion battery at a constant current of magnification C2 until the cut-off voltage V C2 , and let it stand for a second preset time; 3) Charge the sodium ion battery to a cut-off voltage V at a constant current of C3 C3 , leaving it alone for a third preset time; 4) Discharge the sodium-ion battery at a constant current of rate C4 to the cut-off voltage V D , and complete the formation; where P satisfies: 1000Kgf ≤ P < 3000Kgf; C1, C2, C3, and C4 are each independently 0.05C - 0.5C.
2. The formation method according to claim 1, wherein, The sodium-ion battery includes a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte; the positive electrode sheet includes a positive electrode material, the positive electrode material includes an O3-phase layered oxide material, the negative electrode sheet includes a negative electrode material, and the negative electrode material includes a hard carbon material; the electrolyte includes a solvent, an electrolyte sodium salt and an additive.
3. According to claim 1 or the formation method described above, characterized in that, The additive includes at least one of fluoroethylene carbonate, vinylene carbonate, 1,3-propane sultone, and 1,3-dioxolane-2-thione.
4. The formation method according to any one of claims 1-3, characterized in that, The rate C1 is 0.05C - 0.1C; And / or, the rate C2 is 0.1C - 0.15C; And / or, the rate C3 is 0.1C - 0.5C.
5. The formation method according to claim 4, characterized in that, C1, C2 and C3 increase.
6. The formation method according to any one of claims 2-5, characterized in that, The cut-off voltage V C1 is 2.2 - 2.6 V; and / or, the cut-off voltage V C2 is 2.9 - 3.2V; and / or, the cut-off voltage V C3 is 3.9 - 4.1V.
7. The formation method according to any one of claims 1-6, characterized in that, The first preset time, the second preset time, and the third preset time are each independently selected from any value within the range of 5 - 30 min.
8. The formation method according to any one of claims 1-6, characterized in that, The magnification C4 is 0.05C - 0.3C; the cut-off voltage V D is 1.5 - 2.0V.
9. The formation method according to any one of claims 1-8, characterized in that, The P satisfies: 1000 Kgf ≤ P ≤ 1500 Kgf; And / or, the T satisfies: 25°C ≤ T ≤ 40°C.
10. A method for preparing a sodium-ion battery, characterized in that, Including forming using the forming method of the sodium-ion battery according to any one of claims 1 - 9.
11. A sodium-ion battery formed by using the forming method of the sodium-ion battery according to any one of 1 - 9.
Citation Information
Cited By
Method and device for generating solid electrolyte interfacial film
CN120545491A